Analisis Determinasi Profitabilitas Perusahaan Sektor Pertanian di Bursa Efek Indonesia - Munawar, Andri Helmi; Nurjanah, Dara Siti; Hadiani, Dian (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2023)
The purpose of this study is to find out and analyze Operational Costs, Debt to Asset Ratio, Profitability using Return on Assets (ROA) measurements and the magnitude of the influence of Operational Costs and Debt to Asset Ratio on Profitability in the Agricultural Industry Listing on the Indonesia Stock Exchange 2020- 2022. The approach used is a quantitative approach with explanatory methods, secondary data with purposive sampling analysis sampling technique. The statistical method used is multiple linear regression, in addition to that a classic assumption test is also carried out assisted by the SPSS Version 25 for windows program. Based on the results of the analysis that the effect of Operational Costs and Debt to Asset Ratio on Profitability is 27,2%.. The hypothesis test shows that there is a simultaneous influence between Operational Costs and the Debt to Assets Ratio on Profitability. Partially Operational Costs and Debt to Asset Ratio have no effect on Profitability